T and NK cell subset changes with microbial extracts and human HSP60-derived peptides in Behcet's disease - (:unkn) unknown (CLINICAL & EXPER RHEUMATOLOGY, 2004)
Objective. Microorganisms such as streptococcus and autoantigens such as 60 kD heat-shock protein (HSP60) are implicated in the etiopathogenesis of Behcet's disease (BD). Methods. Peripheral blood mononuclear cells front patients with BD (n = 16) and health), controls (HC) (n = 11) were cultured for 5 days with extracts of S. sanguis-KTH-1 (SS), E. coli (EC) and a mixed peptide combination from human HSP60 (aa 136-50, 179-97, 224-58 (and 336-51) reported to be associated with BD. T and NK cell subset changes were determined by flow cytometry. Results. In unstimulated 5-day cultures gammadelta(+) (both CD4(+)gammadelta(+) and CD8(+)gammadelta(+)), CD8(+)alphabeta(+), CD4(+)CD56(+) and CD8(+)-CD11b(+) cells were increased in BD compared to HC. In antigen-stimulated cultures of BD patients CD3(+) and alphabeta(+) T cells responded to HSP60 peptides whereas EC stimulated only CD16/CD56(+) NK cells. In the control group, similar to BD, alphabeta(+) and CD4(+) T cells responded to HSP60 peptides, however SS and EC mainly activated cytotoxic T cell subsets (CD8(+)CD11b and CD4(+)-CD56(+) T cells). Conclusion. Significant increases in unstimulated T cell subsets suggest the presence of an in vivo T cell activation in BD. In both patients and controls similar patterns of responses were observed against different microorganisms, however the role of human. HSP60 peptides as immunodominant, cross-reactive antigens could not be demonstrated.
Keywords: Behcet's disease; streptococcus; Escherichia coli; human HSP60; HEAT-SHOCK-PROTEIN; STREPTOCOCCUS-SANGUIS; GAMMA; ANTIGEN; INDUCTION; EXPANSION; SYMPTOMS; FLORA; KTH-1; BD